Training in Sago-Based Food Processing as An Effort To Strengthen The Community Economy in The District of Nabire, Central Papua Province - Saptarining Wulan; Adhi Trirachmadi Mumin; Doni Muhardiansyah; Alifatqul Maulana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Nabire Regency faces high poverty of 23.90% in 2022 and stunting of 22.2% in 2023, even though it has abundant natural resources. PKM activities aim to improve housewives' skills in processing sago, increase awareness of food diversification, and create new business opportunities, to improve the community's diet and economic independence. The activity, which was carried out in Nabire Regency on 26-29 January 2022, involved 30 housewives from several villages in six groups. The implementation phase was carried out for two days, participants received theory about hygiene and sanitation, followed by freezing and practice in making sago dishes. Evaluation is carried out through pre-tests, post-tests and practical competitions, with prizes for the best participants. PKM activities in Nabire Regency succeeded in increasing the community's knowledge and skills in processing sago through two days of training. Participants learned sago processing techniques and the importance of hygiene and sanitation, with evaluations showing significant increases in knowledge. All groups scored above 70 in cooking practice, and prizes were awarded to the best participants. However, challenges such as limited practice time and equipment emerged, as well as recommendations for improving facilities and providing transportation for future participants.